2014
DOI: 10.1007/s00405-014-2958-x
|View full text |Cite
|
Sign up to set email alerts
|

Delaying partial stapedectomy for otosclerosis: effects on long-term hearing outcomes following surgery

Abstract: The purpose of this study is to evaluate hearing outcomes following partial stapedectomy according to age at the time of surgery and evaluate functional hearing at ≥ 10 years' follow-up, and to assess the effect of delay in surgery on overall functional hearing outcomes. Data were collected from patients operated upon for otosclerosis by a single surgeon from 1990 to 1999. Pure-tone air (PTA), pure-tone bone (PTB), air-bone gap (ABG), air-conduction at 8 kHz (AC 8), bone-conduction at 4 kHz (BC4) and speech di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In the same study, no differences were found in hearing levels between the 2 age groups at 10 or more years after the operation; they concluded that the age (and ABG) of the patients at the time of surgery did not influence the results, which is consistent with our data. In parallel with Maniakas et al [2015] no differences in hearing measurements were found between our 2 groups at any of the postoperative follow-ups. Thus, regardless of the gap size at the time of surgery, overall hearing deterioration evolved similarly in patients with preoperative ABGs of less than or equal to 20 dB and those with more than 20 dB.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In the same study, no differences were found in hearing levels between the 2 age groups at 10 or more years after the operation; they concluded that the age (and ABG) of the patients at the time of surgery did not influence the results, which is consistent with our data. In parallel with Maniakas et al [2015] no differences in hearing measurements were found between our 2 groups at any of the postoperative follow-ups. Thus, regardless of the gap size at the time of surgery, overall hearing deterioration evolved similarly in patients with preoperative ABGs of less than or equal to 20 dB and those with more than 20 dB.…”
Section: Discussionsupporting
confidence: 49%
“…Salmon et al [2015] reported preoperative differences in age (42 and 50 years, respectively) and gender between the small and large ABG groups. Interestingly, Maniakas et al [2015] compared the results of partial stapedectomy in patients under 45 and over 45 years of age and found that younger patients had significantly smaller preoperative ABGs. In the same study, no differences were found in hearing levels between the 2 age groups at 10 or more years after the operation; they concluded that the age (and ABG) of the patients at the time of surgery did not influence the results, which is consistent with our data.…”
Section: Discussionmentioning
confidence: 99%